A bubble-templated approach to holey N/S-codoped carbon nanosheet aerogels with honeycomb-like structure for supercapacitors. (1st February 2022) - Yang, Chao; Jia, Qi; Pan, Qianqian; Qi, Wentao; Ling, Rui; Cao, Bingqiang
Highlights: The polypyrrole precursors were prepared by the bubble-templated polymerization. HNS-CNA-1 possesses a high active N content and abundant holes in nanosheets. The HNS-CNA-1 electrode provides a capacitance of 477 F g −1 at 1 A g −1 in H2 SO4 . The HNS-CNA-1 SC delivers the energy density of 71.7 Wh kg −1 at 1 kW kg −1 . Abstract: Holey graphene with unique in-plane holes at the basal plane of graphene, has shown extraordinary promise for high-rate supercapacitors (SCs), due to its hole architecture that can shorten ion diffusion paths and facilitate electrolyte ion penetration. However, holey graphene is usually fabricated through a chemical etching procedure to create holes, which requires rigorous etching conditions and a cumbersome purification process. We propose a novel holey N/S-codoped carbon nanosheet aerogel (HNS-CNA) with honeycomb-like structure, which can be fabricated through an unprecedented bubble-templated polymerization of pyrrole and the subsequent carbonization of the holey polypyrrole nanosheet hydrogel (H-PPyNH) precursors. The bubble-templated route to H-PPyNH is considered to be promising for large-scale commercialization, due to the superiority of this cost-effective solution procedure. With the voltage window of 2 V, the symmetric HNS-CNA-1 SC delivers a high specific capacitance of 129 F g −1 at 1 A g −1, cycling stability of 90.7% (after 10, 000 cycles) and energy density of 71.7 Wh kg −1 at 1 kW kg −1, attributed to abundant holes and N/S co-doping characteristics, which can facilitate electrolyte ion diffusion and introduce pseudocapacitance respectively. This holey N/S-codoped carbon nanosheet aerogel opens up a facile approach to promising electrode materials for highly-efficient capacitive energy storage. Graphical abstract: Image, graphical abstract